2018
DOI: 10.26637/mjm0601/0016
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the weakly singular Volterra integro-differential equations using He's Homotopy perturbation method

Abstract: In this paper, we present a reliable algorithm for solving a system of Volterra integro-differential equations (VIDE) using He's Homotopy Perturbation Method (HHPM) [9,10] and spectral methods [12]. This method converts a system of Volterra integro-differential equations to the system of linear algebraic equations. Some illustrative examples have been presented to illustrate the implementation of the algorithm and efficiency of the method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In this section, we briefly review the main points of the powerful method, known as the He's homotopy perturbation method [16,19,21]. To illustrate the basic ideas of this method, we consider the following differential equation:…”
Section: He's Homotopy Perturbation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section, we briefly review the main points of the powerful method, known as the He's homotopy perturbation method [16,19,21]. To illustrate the basic ideas of this method, we consider the following differential equation:…”
Section: He's Homotopy Perturbation Methodsmentioning
confidence: 99%
“…If we take He's homotopy perturbation method [14][15][16][17][18][19][20][21] getting applied to the wide class problems in physics, biology and chemical reactions. If provides this result in a computable terms of rapid convergent series.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of studies conducted on FDEs, for instance see [10]- [16], demonstrate that Hukuhara and Seikkala derivatives, despite being equivalent, are more palatable definitions. However, the research results have revealed that these derivatives suffer from a number of major limitations among which the most serious is that the diameter of the fuzzy function under study needs to be necessarily non-decreasing.…”
Section: A Integer Order Fuzzy Differential Equationsmentioning
confidence: 99%